Case report: A case of cutaneous anthrax guided by metagenomic next-generation sequencing technology - Wang, Lu; Wen, Danli; Qu, Yuanqing; Wang, Qin; Liu, Yuan (Frontiers in Medicine, 2024)
Anthrax is an acute zoonotic infectious disease caused by Bacillus anthracis. It is categorized as a Class B (reported within 24 h of onset, including pulmonary anthrax, which is managed as a Class A infectious disease and reported within 2 h of onset) infectious disease in China. Human anthrax infection primarily occurs through direct or indirect contact with infected animals. This study reports a case of cutaneous anthrax where typical anthrax colonies were observed in conventional microbial cultures, and large Gram-positive rods with squared ends were visible under the microscope. The results from metagenomic next-generation sequencing (mNGS) suggested the presence of Bacillus anthracis. This research explores the value of combining traditional microbiology with mNGS technology for the early diagnosis and therapy of infectious diseases.